Contribution to the knowledge of bats (Chiroptera,Mammalia) of Macedonia - Stojanovski, Laste (Macedonian Journal of Ecology and Environment, 1994)
The data of the investigations of Macedonian bats in 1993/94 are presented in this article. Ecology and distribution for six bat species are given: Rhinolophus hipposideros, Rh. ferrumequinum, Pipistrellus pipistrellus., P. kuhli, P. savii and Plecotus austriacus.